Deliberate Self-Poisoning Presenting to an Emergency Medicine Network in South-East Melbourne: A Descriptive Study - Rahman, Asheq; Martin, Catherine; Graudins, Andis; Chapman, Rose (Emergency Medicine International, 2014)
Background. Deliberate self-poisoning (DSP) comprises a small but significant proportion of presentations to the emergency department (ED). However, the prevalence and patient characteristics of self-poisoning attendances to EDs in Victoria have not been recently characterised. Aim. To identify and compare the characteristics of adult patients presenting to the three EDs of Monash Health following DSP. Methods. Retrospective clinical audit of adult DSP attendances between 1st July 2009 and 30th June 2012. Results. A total of 3558 cases over three years were identified fulfilling the search criteria. The mean age of patients was 36.3 years with the largest numbers aged between 18 and 30 (38%). About 30% of patients were born overseas. Forty-eight percent were discharged home, 15% were admitted to ED short stay units, and 5% required ICU admission. The median ED length of stay was 359 minutes (IQR 231–607). The most frequently reported substances in DSP were benzodiazepines (36.6%), paracetamol (22.2%), and antipsychotics (12.1%). Exposure to more than one substance for the episode of DSP was common (47%). Conclusion. This information may help identify the trends in poisoning substances used for DSP in Victoria, which in turn may provide clinicians with information to provide more focused and targeted interventions.